Mitochondrial genome characterization, evolution and intron dynamics of the entomopathogenic genus Cordyceps - Jia, Jinlong; Li, Chengpeng; Tang, Mei; Liao, Hefa; Yang, Zhuliang; Wang, Yanan; Li, Ming; Zeng, Wenbo; Wang, Yuanbing (Frontiers in Microbiology, 2025)
IntroductionCordyceps is a diverse genus of insect-pathogenic fungi, some of which have significant medicinal value.MethodsThe complete mitogenomes of six Cordyceps species (C. cicadae, C. cocoonihabita, C. militaris, C. neopruinosa, C. pruinosa, and C. tenuipes) were sequenced, assembled, and annotated in this study. Additionally, the previously published mitogenome of C. blackwelliae was also included for comparative analysis.ResultsThe mitogenomes of these seven Cordyceps species are circular DNA molecules ranging length from 29,929 to 51,692bp, containing 15 protein-coding genes (PCGs), two rRNAs, and 25–27 tRNAs, as well as four to 21 open reading frames (ORFs). The rps3 gene appears to be under relaxed selection pressure across Cordyceps species. The non-conserved PCGs, such as homing endonucleases and proteins of unknown functions, show dynamic evolutionary patterns, highlighting the genetic diversity among the species. Introns, recognized as key contributors to mitogenome size variation, frequently undergo gain and loss events, further contributing to genomic diversity. The comparative analysis revealed both conserved and variable elements within the mitogenomes of the seven Cordyceps species. Phylogenetic analysis using 14 PCGs generated a well-supported topology that clarified the evolutionary relationships among Cordyceps species.DiscussionIn conclusion, this study provides valuable insights into the conservatism and variability of mitogenomes within the genus Cordyceps, enhancing our understanding of their origin, evolution, and genetic diversity.